From sensory evaluation to operational excellence: A capacity-building program in Tulungagung’s Robusta and Arabica coffee sector - Gautama Sastra Waskita; Nurani; Atina Hidayati; Sutantri; Denny Rakhmad Widi Ashari (Penamas: Journal of Community Service, 2026)
The growing demand for industry-ready human resources in Indonesia’s coffee sector requires vocational students to possess competencies in sensory evaluation and operational coffee skills. This community engagement program aimed to enhance vocational capacity through hedonic–organoleptic assessment and basic barista training among 33 students of the Agricultural Product Quality Control Department at SMKN 1 Tulungagung. The program employed an experiential learning approach integrating training, continuous education, and the Specialty Coffee Association (SCA) cupping protocol. Data were collected using pre-test and post-test assessments, practical observations, and participant feedback. The results demonstrated significant improvements in students’ understanding of sensory attributes, cupping procedures, and coffee operational skills, with increased confidence and competency in evaluating Robusta and Arabica coffee. The program also strengthened participants’ awareness of Indonesia’s coffee industry and vocational readiness. These findings suggest that industry-oriented experiential training effectively supports operational excellence and capacity building in vocational coffee education.